2005
DOI: 10.3748/wjg.v11.i6.791
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pyloriinfection, glandular atrophy and intestinal metaplasia in superficial gastritis, gastric erosion, erosive gastritis, gastric ulcer and early gastric cancer

Abstract: The progression of the gastric pre-cancerous lesions, glandular atrophy and intestinal metaplasia in superficial gastritis, gastric erosion, erosive gastritis and gastric ulcer was strongly related to H pylori infection. In depth studies are needed to evaluate whether eradication of H pylori infection will really diminish the risk of gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
92
3
10

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(112 citation statements)
references
References 35 publications
6
92
3
10
Order By: Relevance
“…In our study, the rate of H. pylori infection was lower in GC cases (60.4%), compared with those in SG (85.0%) and AG (87.7%) cases. Our findings were similar to those obtained in a Chinese study which showed that whereas the rates were 63.3% and 80.8%, respectively, in gastric erosion and gastric ulcer, the overall rate was 52.4% in patients with early gastric cancer, with the rates being 35.0%, 50.7%, 34.6%, respectively, in the antrum, corpus, and incisura of stomach (Zhang et al, 2005). Indeed, it has been shown that development of precancerous and cancerous lesions may create a hostile environment to H. pylori, and thus H. pylori infection may disappear following the development of these lesions (Genta et al, 1993).…”
Section: 215 Wnt Pathway Expression and Hpylori Infection In Gastrisupporting
confidence: 79%
“…In our study, the rate of H. pylori infection was lower in GC cases (60.4%), compared with those in SG (85.0%) and AG (87.7%) cases. Our findings were similar to those obtained in a Chinese study which showed that whereas the rates were 63.3% and 80.8%, respectively, in gastric erosion and gastric ulcer, the overall rate was 52.4% in patients with early gastric cancer, with the rates being 35.0%, 50.7%, 34.6%, respectively, in the antrum, corpus, and incisura of stomach (Zhang et al, 2005). Indeed, it has been shown that development of precancerous and cancerous lesions may create a hostile environment to H. pylori, and thus H. pylori infection may disappear following the development of these lesions (Genta et al, 1993).…”
Section: 215 Wnt Pathway Expression and Hpylori Infection In Gastrisupporting
confidence: 79%
“…O adenocarcinoma gástrico atinge altas taxas de incidência em países orientais como China e Japão, especialmente quando comparadas com as taxas encontradas no ocidente. UEMURA et al (41) (11,44,45) .…”
Section: Resultsunclassified
“…A significância estatística foi obtida através do teste do qui-quadrado, com intervalo de confiança de 95%. v. 44 …”
Section: Métodosunclassified
“…Furthermore, the prevalence rate of gastric cancer has decreased each year [6]. In addition, half of the patients with early gastric cancer are negative for H. pylori antibody [7].…”
Section: Introductionmentioning
confidence: 99%